Management of Child Development Center in the New Normal Era at Wang Yai Subdistrict Administrative Organization, Wichian Buri District, Phetchabun Province - Plonthong, Chamaiporn; Kerdphon Prasopsak, Wasita; Rattanasermpong, Mayuree (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2025)
This study aimed to: 1. examine the management of child development centers during the New Normal era; and 2. propose guidelines for managing child development centers under the responsibility of the Wang Yai Subdistrict Administrative Organization, Wichian Buri District, Phetchabun Province. A mixed-methods approach was employed. The sample consisted of 73 parents whose children attended the center, selected through simple random sampling, and 10 key informants for in-depth interviews. Data collection tools included a 50-item questionnaire and a semi-structured interview protocol, with a reliability coefficient of 0.97. Data were analyzed using percentage, mean, and standard deviation. The research findings revealed that: 1. overall, the management of child development centers during the New Normal era was rated at a very high level. Areas ranked from highest to lowest mean score were: promotion of early childhood development networks, encouragement of participation and support, personnel management, buildings, facilities, environment and safety, center management, and academic and curriculum-based activities; 2. the proposed management guidelines included: (i) fostering collaboration and securing budgetary support from all sectors; (ii) providing training for teachers in technology use; (iii) implementing an alternating attendance schedule for young children; (iv) assigning teachers to conduct home visits to support continuous child development; (v) offering basic early childhood development training for parents; and (vi) building partnerships across networks to exchange knowledge and address challenges in organizing appropriate early childhood education.